Design and chemical synthesis of eukaryotic chromosomes. (2nd November 2017) - Xie, Ze-Xiong; Liu, Duo; Li, Bing-Zhi; Zhao, Meng; Zeng, Bo-Xuan; Wu, Yi; Shen, Yue; Lin, Tao; Yang, Ping; Dai, Junbiao; Cai, Yizhi; Yang, Huanming; et al.
Abstract : We reviewed the design, building, testing and debugging technologies and methodologies for synthesizing designer eukaryotic chromosomes and forecasted their applications. Abstract : Following the discovery of the DNA double helix structure and the advancement of genome sequencing, we have entered a promising stage with regard to genome writing. Recently, a milestone breakthrough was achieved in the chemical synthesis of designer yeast chromosomes. Here, we review the systematic approaches to the de novo synthesis of designer eukaryotic chromosomes, with an emphasis on technologies and methodologies that enable design, building, testing and debugging. The achievement of chemically synthesized genomes with customized genetic features offers an opportunity to rebuild genome organization, remold biological functions and promote life evolution, which will be of great benefit for application in medicine and industrial manufacturing.